A Study on Knowledge, Attitudes, and Practices on Rabies in the Philippines - Bundalian, Reynaldo Jr; Lacson, Monalisa; Bacani, Catherine; Soriano, Dinah Rose; Garing, Agnes; Aquino, Artemio Jr; Policarpio, Archie; Mallari, Joey Kyle; San Jose, Remedios; Bulao, Maria Fe; Tanquilut, Neil; Magsino, Patricia Joy (Kesmas, 2020)
In 2007, the Philippine government passed the Anti-Rabies Act to address rabies in the country. However, rabies is still a major public health concern in many provinces. This study aimed to evaluate the knowledge, attitude, and practices (KAP) of residents on rabies, the Anti Rabies Act, and responsible pet ownership (RPO) in Pampanga, Philippines. A cross-sectional survey was done from October 2017 to February 2018 in 92 randomly selected barangays in the province. Questionnaires were adapted from similar studies. Logistic regression was used to identify factors associated with KAP. Results showed that most people have good knowledge of the Anti-Rabies Act, RPO, and moderate knowledge of rabies. Their attitude toward rabies was appropriate, and on RPO, moderate. The RPO practices by most dog owners were good and moderate for most cat owners. Moreover, the subjects’ area of residence was a significant factor in their knowledge of RPO, and pet ownership status was a significant factor in their RPO attitude. In general, respondents showed satisfactory knowledge; however, there is a need to intensify information and education campaigns in rural areas.